Design principles for advancing higher education sustainability learning through transformative research - Philip Bernert; Matthias Wanner; Nele Fischer; Matthias Barth (Environment, Development and Sustainability, 2022)
A growing number of transformative research practices that redefine the role of science in engaging with local–mostly urban–transformation processes have emerged in recent decades. However, while education is considered a key driver for sustainability transformations, higher education has been slow to develop and implement dedicated, appropriate and effective transformative education programmes and learning modules. In this paper, we present a framework of design principles for transformative learning modules in higher education. These principles are derived from two growing discourses: higher education sustainability learning , and transdisciplinary and transformative research —both of which are centrally anchored in the field of sustainable development and sustainability science. The principles presented provide guidance for course leaders in higher education to create learning modules aimed at enabling students to become engaged in transdisciplinary and transformative research that fosters sustainability transitions in local and urban contexts. We use the Transformative Innovation Lab (TIL)—a learning course developed and tested at two German universities—as an example of how the design principles can be applied. The module, which runs over two semesters, supports Masters students in their process of developing real-world laboratories and exploring urban sustainability transitions through collaborative experimentation with local practice partners. We discuss the factors that enable and limit the implementation of transformative learning modules and outline aspects of the novel roles adopted by lecturers in transformative teaching environments. Moreover, we highlight the need for both institutional change and transformative teaching formats that go beyond transformative research as key for driving universities to take responsibility for collaboratively fostering sustainability transitions in their local contexts.
Keywords: 330; Higher education sustainability learning; Transformative learning; Transformative research; Transdisciplinarity; Real-world laboratories; Design principles